The Relationship Of Physical Activity And Abdominal Circumstances With The Event Of Hypertension In Obesity Women In Malang - Kinanti, Rias Gesang; Andiana, Olivia; Al Haqiqi, Irfan (Indonesian Conditioning Coaches, 2024)
This study aims to analyze the level of relationship between physical activity and abdominal circumference with the incidence of hypertension in women in Malang Raya. The research method is observational using a cross sectional research design. The sample used is 100 people. The sampling technique was carried out by probability sampling or simple random sampling. The independent variables in this study were physical activity and abdominal circumference. The dependent variable is the incidence of hypertension. Respondents' criteria were having female sex, > 50 years old and having an abdominal circumference > 80 cm. Analysis of the data used is the Spearman rank statistical test. The results of the statistical test of physical activity with the incidence of hypertension resulted in a p value = 0.020 or there was a significant level of relationship between physical activity and the incidence of hypertension, with a correlation coefficient value of -0.232, namely the more often you do physical activity, the smaller the degree of hypertension experienced. The results of the statistical test of abdominal circumference with the incidence of hypertension resulted in a p value = 0.002 or there was a significant relationship between abdominal circumference and the incidence of hypertension, with a correlation coefficient value of 0.302, namely the greater the abdominal circumference, the higher the degree of hypertension.